The origins and expansion of the male breadwinner family: The case of nineteenth-century Britain. - Horrell, S; Humphries, J (Cambridge University Press, 1997)
The transition from a family economy in which incomes were democratically secured through the best efforts of all family members to one in which men supported dependent wives and children appears as a watershed in many otherwise very different histories of the family. It looms large in both orthodox economic analyses of historical trends in female participation rates and feminist depictions of a symbiotic structural relationship between inherited patriarchal relationships and nascent industrial capitalism. Both camps agree, as Creighton has recently put it, about “the out-lines of [the] development” of the male breadwinner family. Where they disagree is in “the factors responsible for its origins and expansion”. Why did families move away from an asserted “golden age” of egalitarian sourcing of incomes, which involved husbands, wives and children, to dependence on a male breadwinner who aspired to a family wage? Neo-classical economic historians emphasize the supply conditions, concentrating on income effects from men's earnings, family structure variables and alternatives to women's employment in terms of productive activities in the home. In contrast, dual systems theorists emphasize demand conditions in terms of institutional constraints on women's and children's employment exemplified by the exclusionary strategies of chauvinist trade unions, labour legislation which limited the opportunities of women and children, and the legitimation of men's wage demands by references to their need for a family wage. Our view is that systematic empirical investigation of the male breadwinner family has been lacking, even the timescale of its appearance and development remains obscure. Unless we fill in the outlines with more empirical detail we will never discover the reasons for its origins and expansion.